Pengaruh Motivasi Kerja, Disiplin Kerja, Gaya Kepemimpinan Dan Kepuasan Kerja Terhadap Kinerja Pegawai Dinas Lingkungan Hidup Kabupaten Ponorogo - febrianti, nurdiana (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2020)
This study aims to analyze the work motivation, work discipline, leadership style and job satisfaction on the performance of employees of The Life Environment Service Work Rengency of Ponorogo. This research was held at the office of The Life Environment Service Work Rengency of Ponorogo. Population of this study is an employee The Life Environment Service Work Rengency of Ponorogo. Sample in this study were 78 respondents The Life Environment Service Work Rengency of Ponorogo. The sampling technique used in this study is convenience sampling, then the data in the process of using multiple regression analysis. The results of this study, based on simultaneous test proved that the discipline of work, leadership style, and job satisfaction have a significant effect on employee performance The Life Environment Service Work Rengency of Ponorogo. Partially, work discipline, leadership style, and job satisfaction have a significant effect at a significance level of 5% or 0,05%, while work motivation did not significantly affect performance.The result of the regression R2 analysis, showed that variable work discipline, work motivation, leadership style and job satisfaction can explain the dependent variable employee performance by 48,5% and the remaining 51,5% described other variable.Â Keywords: work motivation, work discipline, leadership style, job satisfaction, employee performance.Â